Long‐term first‐in‐man Phase I/II study of an adjuvant dendritic cell vaccine in patients with high‐risk prostate cancer after radical prostatectomy. Issue 2 (11th November 2021) - Tryggestad, Anne M. A.; Axcrona, Karol; Axcrona, Ulrika; Bigalke, Iris; Brennhovd, Bjørn; Inderberg, Else M.; Hønnåshagen, Turid K.; Skoge, Lisbeth J.; Solum, Guri; Sæbøe‐Larssen, Stein; Josefsen, Dag; Olaussen, Richard W.; et al.
Abstract: Background: Patients with high‐risk prostate cancer (PC) can experience biochemical relapse (BCR), despite surgery, and develop noncurative disease. The present study aimed to reduce the risk of BCR with a personalized dendritic cell (DC) vaccine, given as adjuvant therapy, after robot‐assisted laparoscopic prostatectomy (RALP). Methods: Twelve weeks after RALP, 20 patients with high‐risk PC and undetectable PSA received DC vaccinations for 3 years or until BCR. The primary endpoint was the time to BCR. The immune response was assessed 7 weeks after surgery (baseline) and at one‐time point during the vaccination period. Results: Among 20 patients, 11 were BCR‐free over a median of 96 months (range: 84–99). The median time from the end of vaccinations to the last follow‐up was 57 months (range: 45–60). Nine patients developed BCR, either during ( n  = 4) or after ( n  = 5) the vaccination period. Among five patients diagnosed with intraductal carcinoma, three experienced early BCR during the vaccination period. All patients that developed BCR remained in stable disease within a median of 99 months (range: 74–99). The baseline immune response was significantly associated with the immune response during the vaccination period ( p  = 0.015). For patients diagnosed with extraprostatic extension (EPE), time to BCR was longer in vaccine responders than in non‐responders ( p  = 0.09). Among 12 patients with the International Society of Urological Pathology (ISUP) grade 5 PC, five achieved remission after 84 months, and all mounted immune responses. Conclusion: Patients diagnosed with EPE and ISUP grade 5 PC were at particularly high risk of developing postsurgical BCR. In this subgroup, the vaccine response was related to a reduced BCR incidence. The vaccine was safe, without side effects. This adjuvant first‐in‐man Phase I/II DC vaccine study showed promising results. DC vaccines after curative surgery should be investigated further in a larger cohort of patients with high‐risk PC.